2015
DOI: 10.1002/fld.4021
|View full text |Cite
|
Sign up to set email alerts
|

Implicit LES of free and wall‐bounded turbulent flows based on the discontinuous Galerkin/symmetric interior penalty method

Abstract: between the flexibility of industrial finite volume methods (FVMs) and the accuracy of academic solvers, such as high-order finite difference (FDM) or pseudo-spectral (PSM) methods. Because of their computational compacity, most of these methods-in particular, those with discontinuous interpolation-also provide an excellent serial and parallel computational efficiencies. In view of these advantages, it is mainly in the field of scale-resolving simulations of industrial turbulent flows, that is direct numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…However, we will show that if cell-based communication is used, tight coupling of the implicit-solver is trivial to implement. Furthermore, it will be shown that cell-based communication is not as costly as typically argued [22].…”
Section: Implicit Overset Solvermentioning
confidence: 98%
“…However, we will show that if cell-based communication is used, tight coupling of the implicit-solver is trivial to implement. Furthermore, it will be shown that cell-based communication is not as costly as typically argued [22].…”
Section: Implicit Overset Solvermentioning
confidence: 98%
“…Immense progress has been made in developing discontinuous Galerkin (DG) discretizations for the numerical solution of the compressible Navier-Stokes equations (see, for example, other works [1][2][3][4][5][6] for recent applications to transitional and turbulent flow problems as well as the references therein for details on the discretization methods). In these works, compressible DG solvers are used to also solve incompressible turbulent flow problems by using low Mach numbers instead of considering DG discretizations of the incompressible Navier-Stokes equations.…”
Section: Motivationmentioning
confidence: 99%
“…Their paper devotes particular attention to the analysis of fluid flow physics relying on the computational data extracted from the LES results. De Wiart et al [12] focused on free and wall-bounded turbulent flows within the framework of a Discontinuous Galerkin (DG)/symmetric interior penalty method-based ILES technique. Aspden et al [13] carried out a detailed mathematical analysis of the properties of the ILES techniques comparing simulation results against DNS and LES data.…”
Section: Introductionmentioning
confidence: 99%